A Methodology for Conducting Retrospective Chart Review Research in Child and Adolescent Psychiatry - Gearing, Robin E. (Canadian Academy of Child and Adolescent Psychiatry, 2006)
INTRODUCTION: Retrospective research has become largely undervalued and underutilized in child and adolescent psychiatry with the increasing singular focus on randomized control trials, despite the wealth of clinically relevant data available in historical medical records. In this paper a systematic and scientific approach to chart review research methodology for psychiatry is described. METHOD: Informed by available literature, a methodological stepwise approach for retrospective chart review was developed. RESULTS: A nine step method aimed at maximizing benefits and minimizing limitations is discussed. CONCLUSIONS: Retrospective chart review is an important methodology with distinct advantages and has the potential to provide psychiatry with valuable research opportunities. This method of study should not be lost in the field of psychiatry.